Librariness: a discussion about the essence of the library in times of change - Gallo-León, José-Pablo (Anuario ThinkEPI, 2018)
Librarians have made attempts to transform and adapt libraries in order to avoid obsolescence, but librarians face the opposition of broad sectors of society and the profession. This article discusses the need and opportunity for new services, and considers whether or not changes might pervert the spirit of the library. Even if the need for updating is recognized, these opinions must be taken into account. Therefore, the evolution of the library should be guided by the library´s essence, by its "librariness", which is helping and improving people through information, education, and culture.